The network origins of aggregate fluctuations: A demand-side approach - Emanuele Citera; Shyam Gouri Suresh; Mark Setterfield (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2021)
We construct a model of cyclical growth with agent-based features designed to study the network origins of aggregate fluctuations from a demand-side perspective. In our model, aggregate fluctuations result from variations in investment behavior at firm level motivated by endogenously-generated changes in "animal spirits" or the state of long run expectations(SOLE). In addition to being influenced by their own economic conditions, firms pay attention to the performance of first-degree network neighbours, weighted (to differing degrees) by the centrality of these neighbours in the network, when revising their SOLE. This allows us to analyze the effects of the centrality of linked network neighbours on the amplitude of aggregate fluctuations. We show that the amplitude of fluctuations is significantly affected by the eigenvector centrality, and the weight attached to the eigenvector centrality, of linked network neighbours. The dispersion of this effect about its mean is shown to be similarly important, resulting in the possibility that network properties can result in `great moderations' giving way to sudden increases in the volatility of aggregate economic performance.
Keywords: C63; E12; E32; E37; O41; 330; Aggregate fluctuations; cyclical growth; animal spirits; state of long run expectations; agent-based model; random network; preferential attachment; small world